Crafting the Movement Identity Entrepreneurs in the Swedish Trade Union Movement, 1920-1940 - Jansson, Jenny; Project Muse. (Cornell University Press, 2020)
"Describes how trade union leaders strategically used internal education to form a reformist class identity in the Swedish trade union movement in the 1920s"--
The reformist choice -- Problems identified by the LO leadership -- The solution : a plan for identity management -- Constructing identity -- Implementing the education strategy -- Crafting consensus.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Landsorganisationen i Sverige -- History -- 20th century; Working class -- Sweden -- History -- 20th century; Labor movement -- Sweden -- History -- 20th century; Electronic books